Factors associated with the willingness to receive COVID-19 vaccination among pregnant women - Hana Fathiazzahra Jaelani; Rike Syahniar (International Journal of Public Health Science (IJPHS), 2023)
Pregnant women are a vulnerable group to be infected by COVID-19, and have a higher risk of serious illness, morbidity, and mortality than the general population. Willingness to receive COVID-19 vaccination has a decisive role in successfully controlling the COVID-19 pandemic. The objective of this study was to determine the factors related to the willingness to get COVID-19 vaccination in pregnant women at the Teluknaga Public Health Center. A total of 102 pregnant women with gestational ages of 13 to 33 weeks were selected by convenience sampling. Data were collected by filling out a questionnaire during November to December 2021. All respondents had a health status that meets the requirements for COVID-19 vaccination. Overall, 63% of pregnant women wanted to receive COVID-19 vaccination. There were significant relationships between education (p=0.029), frequency of antenatal care (p=0.019), husband's support (p<0.001) and willingness to receive vaccination. Religion, occupation, knowledge about COVID-19, parity, frequency of antenatal care visits, and sources of information did not show significant relationships with the willingness to receive COVID-19 vaccination among them. Education and awareness campaigns about the safety of the COVID-19 vaccine for pregnant women and the role of health workers are needed to raise awareness.